DrawCode: Visual tool for programming microcontrollers - Mahesh, M.; Sivraj, P. (2017 3rd International Conference on Advances in Computing,Communication & Automation (ICACCA) (Fall), 2017)
For a beginner or someone from a specific application area who has limited skill set in microcontroller programming, it becomes a very tedious task to make a microcontroller, the brain of all automated systems now, up and running for one's application. This work is an attempt to develop a model driven integrated development environment (MD-IDE) for Texas Instruments MSP430g2231 microcontroller that can ease the work of the developers using this microcontroller. The GUI and the core logic of the IDE will be developed using Qt 5.0 framework and validated by programming TI's MS430g2231. The finished work will have an Integrated Development Environment (IDE) where in the user can simply use several predefined blocks each representing a peripheral or a function of the microcontroller. The final IDE can help the user reduce the design time by using a graphical programming methodology, for any micro-controller of his choice by adding xml description of controllers and a header file with the DrawCode specific functions. The application can be further modified by including an option to create user defined modules for peripherals.